Most, but not more than half, is proportion-dependent and sensitive to individual differences - Ramotowska, Sonia; Steinert-Threlkeld, Shane; Van Maanen, Leendert; Szymanik, Jakub (Proceedings of Sinn und Bedeutung, 2020)
In this study we test individual differences in the meaning representations of two natural language quantifiers – most and more than half – in a novel, purely linguistic task. We operationalized differences in meaning representations as differences in individual thresholds which were estimated using logistic regression. We show that the representation ofmost varies across subjects and its verification depends on proportion. Moreover, the choice of the representation of most affects the verification process. These effects are not present for more than half. The study demonstrates the cognitive differences between most and more than half and individual variation in meaning representations.